Results 1 to 2 of 2

Math Help - why does lim(z→e^(πi/4)) (z - e^(πi/4))/(1 + z^4) =...

  1. #1
    Newbie
    Joined
    Jul 2011
    Posts
    9

    why does lim(z→e^(πi/4)) (z - e^(πi/4))/(1 + z^4) =...

    why does
    lim(z→e^(πi/4)) (z - e^(πi/4))/(1 + z^4)
    = lim(z→e^(πi/4)) 1/(4z^3)


    Follow Math Help Forum on Facebook and Google+

  2. #2
    MHF Contributor
    Prove It's Avatar
    Joined
    Aug 2008
    Posts
    11,829
    Thanks
    1602

    Re: why does lim(z→e^(πi/4)) (z - e^(πi/4))/(1 + z^4) =...

    Quote Originally Posted by blueyellow View Post
    why does
    lim(z→e^(πi/4)) (z - e^(πi/4))/(1 + z^4)
    = lim(z→e^(πi/4)) 1/(4z^3)


    L'Hospital's Rule.
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Replies: 4
    Last Post: September 19th 2010, 05:26 PM
  2. is f: x → |x| a function of x?
    Posted in the Calculus Forum
    Replies: 4
    Last Post: June 3rd 2010, 10:09 AM
  3. proof of a limit as n→∞
    Posted in the Calculus Forum
    Replies: 3
    Last Post: May 21st 2009, 04:26 PM

Search Tags


/mathhelpforum @mathhelpforum